Arteriovenous Fistula After Cerebral Venous Sinus Thrombosis - Jian, Low Qin; Wee, Cheo Seng (Bangladesh Journal of Medicine, 2019)
Thrombosis of the deep cerebral vein is a rare entity. Thrombosis of cerebral veins or dural sinus obstructs blood drainage from brain tissue, leading to cerebral parenchymal dysfunction and increased venous and capillary pressure with disruption of the blood-brain barrier. Many conditions are associated with cerebral venous sinus thrombosis. Prothrombotic conditions, malignancy, infection and head injury has been reported as risk factors for cerebral venous sinus thrombosis (CVST). Neuroimaging features of CVST include focal areas of oedema or venous infarction, hemorrhagic venous infarction, diffuse brain edema or rarely subarachnoid haemorrhage. Magnetic resonance imaging of the brain in combination with magnetic resonance venography is the most informative technique in demonstrating the presence of dural thrombus and cortical vein thrombosis. Bangladesh J Medicine Jan 2019; 30(1) : 35-37